2020
DOI: 10.1002/jocb.453
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness in Teams Completing Creative Tasks: Does it Predict?

Abstract: The relationship between conscientiousness and creativity remains equivocal. This is surprising because conscientiousness is a good predictor of job performance across most criteria and occupations. In this longitudinal study, I found support for the achievement striving and the dependability aspects of conscientiousness affecting team member creativity in different ways. Specifically, the achievement striving aspect of conscientiousness positively predicts creative self‐efficacy, but the dependability aspect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 122 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…The relationship involving creativity and conscientiousness is ambiguous ( Kaspi-Baruch, 2019 ) and has remained equivocal. Some scholars are confident there is a positive relationship, while others contend that the relationship is negative, and finally, others have found no relationship whatsoever ( Taggar, 2021 ). Recent scholarship has shown that separately analyzing creative idea generation (e.g., divergent thinking) versus creative production (e.g., creative achievement) reveals that conscientiousness correlates strongly and positively with creative production measures ( Tran et al, 2020 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship involving creativity and conscientiousness is ambiguous ( Kaspi-Baruch, 2019 ) and has remained equivocal. Some scholars are confident there is a positive relationship, while others contend that the relationship is negative, and finally, others have found no relationship whatsoever ( Taggar, 2021 ). Recent scholarship has shown that separately analyzing creative idea generation (e.g., divergent thinking) versus creative production (e.g., creative achievement) reveals that conscientiousness correlates strongly and positively with creative production measures ( Tran et al, 2020 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recent scholarship has shown that separately analyzing creative idea generation (e.g., divergent thinking) versus creative production (e.g., creative achievement) reveals that conscientiousness correlates strongly and positively with creative production measures ( Tran et al, 2020 ). Accordingly, there is a call for a more accurate understanding of the above relationship ( Taggar, 2021 ). Research connecting creativity with low conscientiousness levels has revealed significant positive correlations ( Sadana et al, 2021 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This study examines the importance of TSE and its antecedent variables. Research has called for a better understanding of the relationship between personality and team processes (Taggar, 2020). Our framework answers this call by showing how the Big Five personality traits influence TSE through important motivational needs.…”
Section: Discussionmentioning
confidence: 99%
“…This process stems from manifest needs, collectively, acting as motivators to clarify required steps for these team-based goals. For example, a high need for achievement may trigger perceptions related to positive expectations about future performance, which is directly related to efficacy beliefs (see Taggar, 2020). The clarity associated with such perceptions should provide cognitive structure around successful outcomes related to achievement, power and affiliation (Locke and Latham, 2019).…”
Section: Roles Of Personality and Manifest Needsmentioning
confidence: 99%